Assessment of different radiative transfer equation solvers for combined natural convection and radiation heat transfer problems. (June 2017) - Sun, Yujia; Zhang, Xiaobing; Howell, John R.
Abstract: This work investigates the performance of the DOM, FVM, P1, SP3 and P3 methods for 2D combined natural convection and radiation heat transfer for an absorbing, emitting medium. The Monte Carlo method is used to solve the RTE coupled with the energy equation, and its results are used as benchmark solutions. Effects of the Rayleigh number, Planck number and optical thickness are considered, all covering several orders of magnitude. Temperature distributions, heat transfer rate and computational performance in terms of accuracy and computing time are presented and analyzed. Highlights: Combined natural conveciton and radiation is investigated for many parameters. Effects of different radiation solvers on the Nusselt number are presented. All the methods are compared with the Monte Carlo methods.